2011
DOI: 10.1002/sca.20293
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the activation energy of thiol desorption using lateral force microscopy

Abstract: Thermal stability of self-assembled monolayers (SAMs) is important for applications in various surface science applications. As a model material, 16-mercaptohexadecanoic acid (MHA) on template stripped gold surfaces was investigated to determine the effect of temperature on the change of lateral force signal using atomic force microscopy (AFM). Friction force signals were obtained at various temperatures in order to determine whether it was possible to correlate the friction signal with desorption of the thiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The reported values are between 22 and 32 kcal mol −1 for desorption of different alkylthiols as disulfides. 50,64−69 Our value for the activation energy is at the lower end of these previously reported values likely because of the shorter chain length of our ligand (that decreases the intermolecular chain− chain stabilization), 50,66,68,69 the charge of the terminal functionality, and the high surface curvature of the nanoparticle as compared to planar gold surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 73%
“…The reported values are between 22 and 32 kcal mol −1 for desorption of different alkylthiols as disulfides. 50,64−69 Our value for the activation energy is at the lower end of these previously reported values likely because of the shorter chain length of our ligand (that decreases the intermolecular chain− chain stabilization), 50,66,68,69 the charge of the terminal functionality, and the high surface curvature of the nanoparticle as compared to planar gold surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 73%
“…16−18 Third, a particular parameter of a SAM, such as the contact angle, molecular orientation, structural order, etc., can be monitored, as a fingerprint of temperature-induced changes. 9,16,19,20 Finally, the reaction of a SAM to temperature variation can be traced by spectroscopic techniques, providing insight into the underlying processes. 10,13,19,21−23 The last approach appears to be the most attractive since it provides not local but system-representative information and allows, by a proper choice of experimental tools, to monitor and to understand temperature-induced processes in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal stability certainly depends on the identity of the SAM-forming molecules, the parameters of their self-organization, and the substrate. , This issue can be addressed from different viewpoints. First, the effect of temperature can be monitored by temperature-programmed desorption (TPD), which gives information about the desorption kinetics, characteristic activation energies, and character of desorbed species. , Second, temperature-induced changes can be monitored with molecular precision by scanning tunneling microscopy exposing consecutive structural modifications. Third, a particular parameter of a SAM, such as the contact angle, molecular orientation, structural order, etc., can be monitored, as a fingerprint of temperature-induced changes. ,,, Finally, the reaction of a SAM to temperature variation can be traced by spectroscopic techniques, providing insight into the underlying processes. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the periodicity of the graphene hexagonal structure allowed the observation of the lattice symmetries and determination of the crystal orientation. Liao et al 133 used LFM to analyze the temperature effect on the lateral force signal of 16-mercaptohexadecanoic acid self-assembled monolayers. The LFM signal decreased with the increase in temperature and therefore LFM could be used to analyze the thermodynamic properties of nanomaterials.…”
Section: Lateral Force Imagingmentioning
confidence: 99%